Investigation of hardness and microstructure properties of non alloyed and hardox steel combined with submerged arc welding method - Erden, Mehmet Akif; Gunduz, Suleyman; Caligulu, Ugur; Boz, Mustafa (Gazi Univ, Fac Engineering Architecture, 2018)
In this work, low carbon steel and hardox steel joined by using submerged arc welding under three different conditions. Same welding parameters (325 A, 30-32 V) were used during welding. Welded joints were characterised in terms of hardness test, macro and microstructures. The results indicated that hardox welded joints showed the highest hardness. In addition, as a result of macro and microstructure study, heat affected zone (HAZ) of structural steels were observed much larger.
Tozaltı kaynak yöntemi ile birleştirilen alaşımsız ve hardoks çeliklerin mikroyapı ve sertlik özelliklerinin araştırılması
Keywords: Hardox steels; non-alloyed steels; submerged arc welding metod; mechanical properties